2013
DOI: 10.1007/s00167-013-2396-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the pivot shift by image analysis using the iPad

Abstract: Although some technical corrections, such as testing manoeuvre and recording procedure, are needed to improve the image data sampling using the iPad application, the potential of the iPad application to classify the pivot shift was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 34 publications
3
135
1
1
Order By: Relevance
“…Although some groups have described rotational stress imaging techniques, this has not yet been well-validated and is not widespread in clinical practice or research [23,24].…”
Section: Rotational Stress Imagingmentioning
confidence: 99%
“…Although some groups have described rotational stress imaging techniques, this has not yet been well-validated and is not widespread in clinical practice or research [23,24].…”
Section: Rotational Stress Imagingmentioning
confidence: 99%
“…Muller et al (2015) [52] reported an ICC for intra-tester reliability ranging from 0.913 to 0.999 (95% CI range: 0.319 to 1.000) and ICC for inter-tester reliability of 0.949 (95% CI: 0.542 to 1.000) for iPad software (The PIVOT software, iOS, programming language Objective-C) designed specifically for quantifying the pivot shift test. Nevertheless, Hoshino et al (2013) [56] did quantify the pivot shift test using an iPad tablet (Apple Inc., Cupertino, CA, USA). They concluded that pivot shift measurements using an iPad did provide quantification of rotational stability for ACL-deficient knees.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the subjectivity on the amount of the applied valgus force whilst doing the test leads to difficulties in replicating the test for confirmation [33]. The specificity of the pivot shift test has been shown to be dependent on whether or not the patient is anaesthetized [56]. It ranges from 32% without to 85% with anaesthesia; this result was confirmed by Kuroda et al [34], who theorised that muscular resistance can suppress the pivot shift manoeuver.…”
Section: Pivot Shift Testmentioning
confidence: 97%
“…Short analysis times and a user-friendly interface make the principle of image analysis to an easily applicable tool for the daily clinical work (see Fig. 6) [126][127][128].…”
Section: Image Analysismentioning
confidence: 99%